Painless evidence-based medicine - Dans, Antonio L.; Dans, Leonila F.; Silvestre, Maria Asuncion A. (John Wiley & Sons, 2008)
This concise book presents evidence-based medicine to neophytes in simplified, friendly language. Basic concepts and application of research statistics are presented in simple sequences that are non-threatening even to the mathematically challenged. The authors emphasize two important aspects of appraisal: 1) how directly it provides an answer to the clinical problem at hand and 2) how well results can be generalized to various populations. Painless Evidence-Based Medicine:.:.; Offers a simplified approach to the complex or technical subject of evidence-based medicine, in terms of presentation.